THE IMPACT OF INSTRUCTIONAL STRATEGIES AND EDUCATIONAL TECHNOLOGY AVAILABILITY ON LEARNING EFFECTIVENESS: THE MEDIATING ROLE OF STUDENT ENGAGEMENT AMONG VOCATIONAL TRAINING INSTRUCTORS - Sairah; Rustandi, Tata; Khaeruman (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
This study aims to examine the impact of instructional strategies and the availability of educational technology on learning effectiveness through student engagement in Vocational Training Institutions in Karawang Regency, Indonesia. The research addresses a gap in the non-formal education literature by elucidating the mediating mechanism of student engagement within an integrated structural model. An explanatory quantitative approach was employed using a cross-sectional design. Data were analyzed through Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The sample consisted of 185 teachers selected through proportional random sampling from a population of 208 teachers. The findings indicate that instructional strategies significantly influence learning effectiveness (? = 0.562; p < 0.001) and student engagement (? = 0.410; p < 0.001). The availability of educational technology also significantly affects learning effectiveness (? = 0.429; p < 0.001) and student engagement (? = 0.408; p < 0.001). Furthermore, student engagement has a significant positive effect on learning effectiveness (? = 0.408; p < 0.001). The R² value demonstrates that the model explains 66.5% of the variance in learning effectiveness. Mediation analysis confirms that student engagement partially mediates the relationship between both exogenous variables and learning effectiveness. These findings highlight that improving learning effectiveness in vocational training institutions depends not only on instructional strategies and technological availability but also on their capacity to foster active student engagement.